Formula feed preparation: helping reduce the risks; a systematic review. Issue 10 (19th September 2003) - Renfrew, M J; Ansell, P; Macleod, K L
Abstract : Aims: To assess what is known about the risks associated with errors in reconstituting the present generation of infant formula feeds, and to examine which methods are likely to be safest. Methods: Systematic review, and examination of the range of infant formula products currently on sale in the UK. Studies from developed countries conducted after 1977 were included. All studies investigating the reconstitution of formula feeds for full term, healthy babies were eligible. Parameters studied were: measures of accuracy of feed reconstitution including fat, protein, total solids, energy content, and osmolality of feed; weight of powder in scoop; and reported method of preparing feed and measuring powder. Formula products were collected from one large UK supermarket in 2002. Number of different types of infant formula preparations available for sale were determined, together with scoop sizes for powdered preparations. Results: Only five studies were identified, none of adequate quality or size. All found errors in reconstitution, with a tendency to over-concentrate feeds; under-concentration also occurred. Thirty one different formula preparations were available for sale in one UK supermarket, with a range of scoop sizes. Some preparations had never been tested. Conclusions: There is a paucity of evidence available to inform the proper use of breast milk substitutes, and a large array of different preparations for sale. Given the impact incorrect reconstitution of formula feeds can have on the health of large numbers of babies, there is an important and urgent need to examine ways of minimising the risks of feed preparation.